Answer
a) i) \( a^{3} - \frac{1}{a^{3}} \)
ii) \( a^{2} + \frac{1}{a^{2}} - 2 \)
b) i) 11
ii) 36
Solution
Certainly! Let's tackle each part of the problem step by step.
---
## **4. Complete the following.**
### **a) Simplify:**
#### **i) \( \left(a - \frac{1}{a}\right)\left(a^{2} + 1 + \frac{1}{a^{2}}\right) \)**
**Solution:**
We can simplify the expression by expanding the multiplication:
\[
\left(a - \frac{1}{a}\right)\left(a^{2} + 1 + \frac{1}{a^{2}}\right)
\]
Multiply each term in the first parenthesis by each term in the second parenthesis:
\[
= a \cdot a^{2} + a \cdot 1 + a \cdot \frac{1}{a^{2}} - \frac{1}{a} \cdot a^{2} - \frac{1}{a} \cdot 1 - \frac{1}{a} \cdot \frac{1}{a^{2}}
\]
Simplify each term:
\[
= a^{3} + a + \frac{a}{a^{2}} - \frac{a^{2}}{a} - \frac{1}{a} - \frac{1}{a^{3}}
\]
\[
= a^{3} + a + \frac{1}{a} - a - \frac{1}{a} - \frac{1}{a^{3}}
\]
Notice that some terms cancel out:
\[
a - a = 0 \quad \text{and} \quad \frac{1}{a} - \frac{1}{a} = 0
\]
So, we're left with:
\[
= a^{3} - \frac{1}{a^{3}}
\]
**Final Answer:**
\[
\left(a - \frac{1}{a}\right)\left(a^{2} + 1 + \frac{1}{a^{2}}\right) = a^{3} - \frac{1}{a^{3}}
\]
---
#### **ii) \( \left(a - \frac{1}{a}\right)^{2} \)**
**Solution:**
Expand the square using the formula \((x - y)^2 = x^2 - 2xy + y^2\):
\[
\left(a - \frac{1}{a}\right)^{2} = a^{2} - 2 \cdot a \cdot \frac{1}{a} + \left(\frac{1}{a}\right)^{2}
\]
Simplify each term:
\[
= a^{2} - 2 \cdot 1 + \frac{1}{a^{2}}
\]
\[
= a^{2} + \frac{1}{a^{2}} - 2
\]
**Final Answer:**
\[
\left(a - \frac{1}{a}\right)^{2} = a^{2} + \frac{1}{a^{2}} - 2
\]
---
### **b) Calculate the value of:**
#### **i) \( a^{2} + \frac{1}{a^{2}} \), if \( a - \frac{1}{a} = 3 \)**
**Solution:**
We are given:
\[
a - \frac{1}{a} = 3
\]
Square both sides to find \( a^{2} + \frac{1}{a^{2}} \):
\[
\left(a - \frac{1}{a}\right)^{2} = 3^{2}
\]
Expand the left side:
\[
a^{2} - 2 \cdot a \cdot \frac{1}{a} + \frac{1}{a^{2}} = 9
\]
Simplify:
\[
a^{2} - 2 + \frac{1}{a^{2}} = 9
\]
Now, solve for \( a^{2} + \frac{1}{a^{2}} \):
\[
a^{2} + \frac{1}{a^{2}} = 9 + 2 = 11
\]
**Final Answer:**
\[
a^{2} + \frac{1}{a^{2}} = 11
\]
---
#### **ii) \( a^{3} - \frac{1}{a^{3}} \)**
**Solution:**
We can use the identity:
\[
a^{3} - \frac{1}{a^{3}} = \left(a - \frac{1}{a}\right)\left(a^{2} + 1 + \frac{1}{a^{2}}\right)
\]
From part **b.i**, we have:
\[
a - \frac{1}{a} = 3 \quad \text{and} \quad a^{2} + \frac{1}{a^{2}} = 11
\]
Substitute these values into the identity:
\[
a^{3} - \frac{1}{a^{3}} = 3 \cdot (11 + 1) = 3 \cdot 12 = 36
\]
**Final Answer:**
\[
a^{3} - \frac{1}{a^{3}} = 36
\]
---
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution